Investigation on Potential of Green Area for Establishment of Forest in University Campus - Muhammad Asyraf Yusoff; Rahayu Ahmad; Sanusi Mohammed; Mohamad Arif Iskandar Abdul Wahab; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page:48-61